Diseño e implementación de un prototipo inteligente mediante el uso de sistemas embebidos, tecnología inalámbrica y aplicación móvil para monitorear los niveles de glucosa. - Nivelo Andrade, Jhandry Alfredo (2024)
This research project focuses on the design and implementation of an intelligent prototype for monitoring glucose levels, employing embedded systems, wireless technology, and a mobile application. Its goal is to provide users with an accessible and easy-to-use health management tool. Real-time data collection is achieved autonomously through embedded systems, while wireless technology facilitates the transmission of this data to the corresponding mobile application. This app features an intuitive interface for visualizing and analyzing glucose levels and displaying alerts. The development of the Curricular Integration Work was divided into five phases: research, data collection, software selection, design, simulation and development, implementation, and evaluation. For this, components such as the Bluetooth module, the Arduino Nano, and the LM324 quad operational amplifier were used. These elements were fundamental in creating essential circuits, such as the voltage divider, the current-to-voltage converter, and the potentiostat circuit. While the voltage divider is responsible for measuring the voltage of the glucose test strip and converting it into a comprehensible signal, the current-to-voltage converter amplifies the signal produced by the test strip. It converts it into a processable voltage signal. For its part, the potentiostat circuit regulates the current applied to the test strip during measurements. Finally, once the various systems of the prototype were implemented, the design and operational specifications were validated through field testing. Simultaneously, a financial analysis was conducted to evaluate the costs associated with the prototype's implementation and compare them with existing models on the market. Keywords: mobile application, electronic and integrated circuits, glucose monitoring, intelligent prototypes, embedded systems, wireless technology.